Trapianto renale da donatore vivente - Aris Tsalouchos; Maurizio Salvadori (AboutScience Srl, 2021)
Kidney transplant is the best therapy to manage end-stage kidney failure. The main barriers limiting this therapy are scarcity of cadaveric donors and the comorbidities of the patients with end-stage kidney failure, which prevent the transplant. Living kidney donor transplant makes it possible to obviate the problem of scarcity of cadaveric donor organs and also presents better results than those of cadaveric transplant. The principal indication of living kidney donor transplant is preemptive transplant. This allows the patient to avoid the complications of dialysis and it has also been demonstrated that it has better results than the transplant done after dialysis has been initiated. Priority indications of living donor transplant are also twins and HLA identical siblings. We also have very favorable conditions when the donor is young and male. On the contrary, the living donor transplant will have worse results if the donors are over 60-65 years and the recipients are young, and this can be a relative contraindication. There is an absolute contraindication for the living donation when the recipient has diseases with high risk of aggressive relapse in the grafts: focal and segmental hyalinosis that had early relapse in the first transplant; atypical hemolytic uremic syndrome due to deficit or malfunction of the complement regulatory proteins; early development of glomerulonephritis due to anti-glomerular basement membrane antibody in patients with Alport syndrome; primary hyperoxaluria. Extreme caution should also be taken in the evaluation of the kidney donors. The risks of developing renal failure or other complications are low if an adequate pre-donation evaluation has been made according to the international guidelines.